Social Problem Solving in Women with PTSD and Addiction - Tajeryan, Zeynab; Afrooz, Gholam Ali; Nouryghasemabadi, Robabeh (Psychology of Woman Journal, 2022)
The present study investigates social problem solving in women with PTSD and addiction. The research design is ex-post facto. The number of participants is 179, including 56 women with PTSD without a history of addiction, 51 women with PTSD and addiction, 39 women with addiction, and 33 normal women without a history of substance use and severe psychological disorders. The PTSD groups were divided based on the duration of the disorder into two groups: those with less than one year and those with more than one year, with 25 individuals randomly assigned to each group. The tools used for assessment were the Social Problem-Solving Inventory-Revised (SPSI-R) and the PTSD Checklist for DSM-5 (PCL-5). The research findings indicated significant differences between the addicted and non-addicted groups in all three variables: positive problem orientation, rational problem solving, and total constructive problem-solving scores. The findings suggested that there were significant differences in all three subscales of dysfunctional problem solving and its overall score.